Pengembangan Wisata Islami: Strategi Pemasaran Wisata Halal di Bumi Syariah - Muhammad Saleh; Kamaruzzaman Kamaruzzaman; Harjoni Desky (Owner : Riset dan Jurnal Akuntansi, 2022)
The objectives of this study are first, to find out the potential for halal tourism in Aceh; second, knowing what efforts have been made by the Aceh government and related parties in the development of halal tourism; and third knowing the strategy that should be done in marketing halal tourism in Aceh. This study used qualitative research methods. The data analysis technique consists of three steps, namely data reduction, data presentation and drawing conclusions. The results show that the potential for halal tourism is not only tourist destinations, but also cultural uniqueness, natural charm, culinary and community friendliness. Efforts in the development of halal tourism are carried out by involving the private sector and the government in an energetic manner in the context of developing halal tourism in Aceh. The strategy carried out in marketing halal tourism in Aceh with 3 programs, namely: a. Marketing concept based on destination, origin, time; b. The promotion strategy is in branding, advertising, and selling; and c. Media strategy, through endorsers, social media, as well as general media. Dissemination of information is very important so that the promotion reaches the goal. This strategy is also usually carried out at the same time as the sales period in various regions and countries of the promotion. When the government participates in halal tourism exhibitions abroad.